2014
DOI: 10.7314/apjcp.2014.15.12.4909
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Malignant Ovarian Germ-Cell Tumors Treated in Chiang Mai University Hospital over a Nine Year Period

Abstract: Malignant ovarian germ cell tumors (MOGCT) are rare neoplasms that most frequently occur in women at a young reproductive age. There have been limited data regarding this disease from Southeast Asian countries. We therefore conducted a retrospective study to analyze the clinical characteristics and the treatment outcomes of MOGCT treated at our institute between January, 2003 and December, 2012. Seventy-six patients were recruited from this period with the mean age of 21.6 years and 11.8% were pre-puberty. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Resection after chemotherapy may be safer than primary tumor resection. Single chemotherapy with methotrexate is beneficial for gestational choriocarcinoma in the mother, but not improve the outcome in children [16]. In this case, the patient treated with BEP regimen due to the diagnosis tend to the nongestational choriocarcinoma.…”
Section: Discussionmentioning
confidence: 86%
“…Resection after chemotherapy may be safer than primary tumor resection. Single chemotherapy with methotrexate is beneficial for gestational choriocarcinoma in the mother, but not improve the outcome in children [16]. In this case, the patient treated with BEP regimen due to the diagnosis tend to the nongestational choriocarcinoma.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, Mangili et al [17], announced a recurrence rate of 18% in a study of 123 patients of MOGT among whom dysgerminoma was 40% and stage I was 71%. Additionally, Neeyalavira & Suprasert [32] (76 patients) reported 12 recurrent cases (15.8%). Dysgerminoma constituted only 25%, however, stage 1 in their series represented 67%.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent Tai study of 76 patients, Neeyalavira showed that the most common histology of malignant ovarian germ cell tumors was immature teratomas (34.2%). Nevertheless according to Smith, rates for immature teratomas are higher for Asian/Pacific Islanders and Hispanics than Caucasians [12,13]. More specifically, immature formations of teratomas are classified into three categories: firstly, lesions that include immature ectodermic tissue and neuroectodermal epithel in rosettes and tubules, secondly, masses that contain immature mesenchyme with immature cartilage, immature fat, osteoids and rhabdomyoblasts and finally immature endodermal tissue as well as hepatic tissue, intestinal type epithel with basal vacuolization and embryonic renal tissue [1].…”
Section: Discussionmentioning
confidence: 99%